PUBLIC INFORMATION SERVICES OF REGIONAL SPORTS FEDERATIONS: DEMAND AND SUPPLY SITUATION SURVEY - Alabuzhev, S.A.; Knyazev, A.P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the demand and supply situation for the sports federation information services including the information resource demand surveys of different population groups. Methods and structure of the study. The first stage of the study was designed to analyze the sports federations information resource demand statistics, their contents and update frequencies for the Udmurt Republic sports federations (n= 78). And then a questionnaire survey was run to profile the population group demands for the sports federation information resources, their update frequencies, contents and data flows on the whole. We sampled for the questionnaire survey 145 people including 55 coaches (37.9%), 39 sports activists (26.9%), 25 professional athletes (17.2%), 19 physical education and sports managers (13.1%) and 7 practicing instructors (4.8%). Results and conclusion. The sports federation information resource users reported the highest interest in the following sports federation information: news, reports, event schedules, regulations of competitions and final reports; and the lowest interest in referees, ratings and picked team members. The survey also found 71% of the sample needing the information on a daily basis and 29% prepared for delays of a few days. The survey data and analyses may be helpful for the sports federation data flow structuring and prioritizing purposes and selections of the best websites and contents of special interest for the potential users.